Analisis Ketersediaan, Kondisi, dan Kendala dalam Penggunaan Media Komponen Instrumen Terpadu IPA di Sekolah Dasar - Angreni, Siska; Sari, Rona Taula (Universitas Ahmad Dahlan, 2017)
Penelitian ini bertujuan menganalisis ketersediaan, kondisi dan kendala dalam pemanfaatan media Komponen Instrumen Terpadu (KIT) dalam pembelajaran IPA di SD Negeri Kec. Siulak Mukai dan SDN Kec. Siulak. Metode yang digunakan adalah metode deskriptif dengan bentuk penelitian survei. Instrumen yang digunakan lembar observasi dan angket. Hasil penelitian ketersediaan media KIT IPA di SD Negeri Kecamatan Siulak Mukai lebih banyak daripada di SD Negeri Kecamatan Siulak, sedangkan kondisi media KIT IPA di SD Negeri Kecamatan Siulak lebih baik daripada di SD Negeri Kecamatan Siulak Mukai. Ketersediaan dan kondisi media KIT IPA di kedua kecamatan tersebut pada umumnya sudah memungkinkan untuk digunakan dalam proses pembelajaran. Adapun kendala yang di alami dalam pemanfaatan media KIT IPA antara lain sulitnya memilih jenis alat yang akan digunakan serta keterampilan guru yang masih kurang dalam memanfaatkan media KIT IPA.Â Analysis of Availability, Condition, and Constraints in the Use of Integrated Component Media in Primary Schools.This research aims to analyze availability, condition and the obstacles for utilization the Integrated of Instrument Components media (KIT) the learning of science at Elementary schools in DistrictÂ Siulak Mukai and at Elementary schools in DistrictÂ Siulak. The research applied a descriptive method which included survey forms. Instruments used observation sheets and quesioner. The result of the researchÂ showed that the availability of Integrated Instrument Components media (KIT) of natural science at Elementary schools at DistrictÂ Siulak Mukai was much higher than at Elementary schools at DistrictÂ Siulak, while as the condition of Integrated Instrument Components media (KIT) of natural science at Elementary schools in District Siulak was better than at Elementary schools in DistrictÂ Siulak Mukai. The availability and condition of Integrated Instrument Components media (KIT) of natural science in both sub-districts are generally possible to be used in the learning process. The obstacles are founded in the utilization of Integrated Instrument Components media (KIT) of natural science, such as the difficulty in choosing equipment type which will be used. Then, teacherâs skills are still lack in utilizing the Integrated Instrument Components media (KIT) of natural science.